Positive electrode active material, electrochemical device and electronic device

JP7626570B6Active Publication Date: 2025-03-14CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023525942
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-26
Filing Date
2022-03-04
Publication Date
2025-03-14
Estimated Expiration
2042-03-04

AI Technical Summary

Benefits of technology

【0016】 本願に提供される技術案は、少なくとも以下の有益的な効果を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626570000004
    Figure 0007626570000004
  • Figure 0007626570000005
    Figure 0007626570000005
  • Figure 0007626570000001
    Figure 0007626570000001
Patent Text Reader

Abstract

The present application provides positive electrode active materials, electrochemical devices, and electronic devices. [Solution] The positive electrode active material includes a conductive substrate and an active material distributed in the conductive substrate, the active material having a core-shell structure, which is composed of a core layer material and a shell layer material. The core layer material includes a phosphate-based sodium salt material, the shell layer material includes a metal oxide, and the conductive substrate includes a carbon material. The positive electrode active material, electrochemical device, and electronic device provided herein effectively improve the conductivity of the positive electrode active material, improve the gram capacity and dynamic properties of the material, and reduce the occurrence of side reactions, thereby improving the cycle performance of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED PATENT APPLICATIONS This application claims priority to Chinese Patent Application No. 202110742609.6, filed on June 26, 2021, entitled "Positive Electrode Active Material, Electrochemical Device and Electronic Device," which is incorporated herein by reference in its entirety.

[0002] The present application relates to the field of secondary battery technology, specifically to positive electrode active materials, electrochemical devices, and electronic devices. [Background technology]

[0003] As energy and environmental problems become more evident, new energy industries have become more important. Lithium-ion batteries have been widely used as important new energy storage devices in recent years due to their characteristics such as high energy density and good cycle characteristics. However, lithium-ion batteries face severe problems such as the shortage of related active material resources, the constant high battery cost, and the depletion of related resources, so there is a need to develop another low-cost metal-ion secondary battery system.

[0004] Sodium-ion batteries have become a research hotspot in recent years due to their advantages of low cost, abundant sodium metal resources, and similar manufacturing process to lithium-ion batteries. In sodium-ion secondary battery systems, pyrophosphate-based positive electrode materials have attracted widespread attention due to their good cycle characteristics and low cost. However, pyrophosphate-based positive electrode materials themselves have poor electrical conductivity, which affects the gram capacity of pyrophosphate-based positive electrode materials when used as is, and their electrochemical performance is poor, which significantly hinders their large-scale application. Summary of the Invention [Problem to be solved by the invention]

[0005] The present application provides a positive electrode active material, an electrochemical device, and an electronic device that can effectively improve the conductivity of the positive electrode active material, improve the gram capacity and dynamic properties of the material, and reduce the occurrence of side reactions to improve the cycle performance of the positive electrode active material. [Means for solving the problem]

[0006] In a first aspect, the present application provides a cathode active material comprising a conductive substrate and an active material having a core-shell structure comprising a core layer material and a shell layer material distributed in the conductive substrate, wherein the core layer material comprises a phosphate-group sodium salt material, the shell layer material comprises a metal oxide, and the conductive substrate comprises a carbon material.

[0007] According to an embodiment of the first aspect of the present application, the metal oxide comprises at least one of WO3, Al2O3, ZnO, CuO, and TiO2.

[0008] According to an embodiment of the first aspect of the present application, the positive electrode active material has at least one of the following characteristics: (1) The chemical formula of the sodium phosphate material is Na x1 R y1 (PO4) Z1 wherein 1≦x1≦3, 1≦y1≦2, and 1≦z1≦3, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (2) The chemical formula of the sodium phosphate material is Na x2 R y2 (P2O7) Z2 wherein 1≦x2≦7, 1≦y2≦3, and 1≦z2≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (3) The chemical formula of the sodium phosphate material is Na x3 R y3 (PO4) Z3 (P2O7)k3 wherein 1≦x3≦7, 1≦y3≦4, 1≦z3≦2, 1≦k3≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (4) The chemical formula of the sodium phosphate material is Na x4 R y4 (PO4) Z4 M l1 wherein 1≦x4≦3, 1≦y4≦2, 1≦z4≦2, and 1≦l1≦3; R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; and M includes at least one of F, Cl, and Br.

[0009] According to an embodiment of the first aspect of the present application, the phosphate sodium salt material comprises at least one of NaFePO4, Na3V2(PO4)3, Na2FeP2O7, Na2MnP2O7, NaCoP2O7, Na7V3(P2O7)4, Na2FePO4F, Na3V2(PO4)2F3, Na4Fe3(PO4)2(P2O7), Na4Mn3(PO4)2(P2O7), Na4Co3(PO4)2(P2O7), Na4Ni3(PO4)2(P2O7), Na7V4(PO4)(P2O7)4.

[0010] According to an embodiment of the first aspect of the present application, the mass of actual oxygen atoms in the metal oxide is 70% to 95% of the mass of theoretical oxygen atoms in the metal oxide.

[0011] According to an embodiment of the first aspect of the present application, the positive electrode active material has at least one of the following characteristics: (5) The shell layer material has a thickness of 50 nm to 400 nm. (6) The mass content of the shell layer material in the positive electrode active material is 1% to 10%. (7) The mass content of the core layer material in the positive electrode active material is 90% to 99%. (8) The mass content of the conductive base material in the positive electrode active material is 1% to 10%.

[0012] According to an embodiment of the first aspect of the present application, the positive electrode active material has at least one of the following characteristics: (9) The carbon material includes at least one of carbon nanotubes, graphene, carbon fibers, natural graphite, and artificial graphite. (10) The carbon material contains an oxygen-containing group, and the oxygen-containing group is at least one type selected from a carboxyl group, a hydroxyl group, and an ether group. (11) The carbon material contains an oxygen-containing group, and the mass content of oxygen atoms in the carbon material is ≧0.1%. (12) The conductive substrate is a carbon material.

[0013] According to an embodiment of the first aspect of the present application, the positive electrode active material has at least one of the following characteristics: (13) The positive electrode active material has a resistivity of 0.005 Ω·cm to 100 Ω·cm at a pressure of 20 MPa. (14) The positive electrode active material has an average particle size of 5 μm to 20 μm. (15) The positive electrode active material has a gram capacity of 100 mAh / g to 180 mAh / g.

[0014] In a second aspect, the present application provides an electrochemical device comprising a positive electrode sheet comprising the above-described positive electrode active material, a negative electrode sheet, a separator, and an electrolyte.

[0015] In a third aspect, the present application provides an electronic device comprising an electrochemical device as described above. Effect of the Invention

[0016] The technical solution provided in this application has at least the following beneficial effects:

[0017] The present application provides a positive electrode active material in which the surface of a sodium phosphate material is coated with a metal oxide, and since the metal oxide has a relatively high mechanical strength, the stability of the coating layer can be maintained even if the volume changes due to the charge and discharge of the material, and the metal oxide has a large amount of oxygen vacancies, which provides a certain electrical conductivity. In addition, the metal oxide can form a metal sodium salt with shuttled sodium ions having a high sodium ion conductivity to improve the dynamic properties of the material. From the above, the coating layer can improve the electrical conductivity of the sodium phosphate material to improve its gram capacity and dynamic properties, while preventing the sodium phosphate material from directly contacting the electrolyte, reducing the occurrence of side reactions, and improving the cycle performance of the positive electrode active material. By attaching the coated active material to a conductive substrate, the electrical conductivity of the material can be further improved by utilizing the high electrical conductivity of the conductive substrate, and the positive electrode active material having a conductive polymer coated structure and a conductive substrate can exhibit a higher gram capacity, better dynamic properties and cycle performance. [Brief description of the drawings]

[0018] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings used in the embodiments are briefly introduced below. It should be understood that the following drawings only illustrate some embodiments of the present application, and are not to be regarded as limiting the scope of the present application.

[0019] [Figure 1] FIG. 2 is a schematic diagram showing the configuration of one type of positive electrode active material provided in the present application. [Diagram 2] FIG. 2 is a schematic diagram showing the configuration of an active material in a positive electrode active material provided in an example of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be described in more detail with reference to the drawings and examples. It should be understood that the specific embodiments described herein are only for the purpose of illustrating the present application, and are not intended to limit the present application.

[0021] In the description herein, the terms "first" and "second" are used for descriptive purposes only, unless otherwise specified and limited, and should not be understood as indicating or implying relative importance. The term "plurality" means two or more than two, unless otherwise specified and explained. The terms "connected", "fixed", etc. should be understood broadly, for example, "connected" may be a fixed connection, a detachable connection, an integral connection, or an electrical connection, and may be directly connected or indirectly connected via an intermediate medium.

[0022] The specific meanings of the above terms in this application can be understood by those of skill in the art in light of particular circumstances.

[0023] In the description of this specification, directional terms such as "above" and "below" described in the embodiments of the present application are described in terms of angles shown in the drawings, and should not be understood as limiting the embodiments of the present application. In addition, when the context refers to an element being connected "above" or "below" another element, it should be understood that it can be directly connected to the "above" or "below" of another element, but also can be indirectly connected to the "above" or "below" of another element via an intermediate element.

[0024] In a first aspect, the present application provides a positive electrode active material, and FIG. 1 is a schematic diagram of the positive electrode active material provided in the examples of the present application. As shown in FIG. 1, the positive electrode active material includes a conductive substrate 1 and an active material 2 distributed on the conductive substrate 1. The active material 2 has a core-shell structure, and FIG. 2 is a schematic diagram of the active material in the positive electrode active material provided in the examples of the present application. As shown in FIG. 2, the core-shell structure is composed of a core layer material 21 and a shell layer material 22. Among them, the core layer material 21 includes a phosphate group sodium salt material, the shell layer material 22 includes a metal oxide, and the conductive substrate 1 includes a carbon material.

[0025] In the present application, the conductive substrate 1 is used to construct a conductive network, and the active material 2 may be adhered to the surface of the conductive substrate 1 or may be attached to the pore structure of the conductive substrate 1, but is not limited thereto. By attaching the active material 2 to the conductive substrate 1, the conductive performance of the positive electrode active material can be improved by utilizing the high conductivity of the conductive substrate.

[0026] In the above-mentioned solution, the conductive substrate 1 is a carbon material, in which the carbon material includes at least one of carbon nanotubes, graphene, carbon fiber, natural graphite, and artificial graphite. Specifically, the carbon material includes an oxygen-containing group, and the oxygen-containing group is at least one selected from a carboxyl group, a hydroxyl group, and an ether group. The mass content of oxygen atoms in the oxygen-containing group is ≧0.1%, and optionally, the mass content of oxygen atoms in the oxygen-containing group may be specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., and is not limited thereto. By controlling the mass content of oxygen atoms in the carbon material, the overpotential of the conductive substrate can be reduced, the occurrence of poor affinity between the active material and the positive electrode current collector can be improved, and the adhesion between the active material and the positive electrode current collector can be enhanced.

[0027] In the actual application process, the mass content of the conductive substrate 1 in the positive electrode active material is 1% to 10%, and optionally, the mass content of the conductive substrate in the positive electrode active material may be specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and is not limited here. If the mass content of the conductive substrate 1 in the positive electrode active material is too large, the amount of carbon material with a large specific surface area, no capacity, and low compaction density becomes too large, and the battery capacity becomes small, resulting in a decrease in the energy density and cycle life of the battery. If the mass content of the conductive substrate 1 in the positive electrode active material is too low, the conductive network between the active materials 2 is difficult to effectively form, the conductive speed decreases, and the conductive performance and life of the battery are reduced. Preferably, the mass content of the conductive substrate 1 in the positive electrode active material may be 4% to 8%.

[0028] In the above-mentioned scheme, the active material 2 on the conductive substrate 1 has a core-shell structure, the core-shell structure is composed of a core layer material 21 and a shell layer material 22, the core layer material 21 is coated with the shell layer material 22, the coating structure is full coating or half coating, the coating method may be a solid-phase coating method, a liquid-phase coating method or a gas-phase coating method, etc., the specific coating method may be selected according to need, and is not limited here. Specifically, the shell layer material 22 and the core layer material 21 of the active material 2 are attracted to each other by the Coulombic attraction of charges, or are adhered to each other by a strong chemical bond between the core layer material 21 and the shell layer material 22.

[0029] Specifically, the core layer material 21 contains a sodium phosphate salt material as a component, and the chemical formula of the sodium phosphate salt material is Na x1 R y1 (PO4) Z1 , Na x2 R y2 (P2O7) Z2 , Na x3 R y3 (PO4) Z3 (P2O7) k3 , Na x4 R y4 (PO4) Z4 M l1 wherein 1≦x1≦3, 1≦y1≦2, 1≦z1≦3, 1≦x2≦7, 1≦y2≦3, 1≦z2≦4, 1≦x3≦7, 1≦y3≦4, 1≦z3≦2, 1≦k3≦4, 1≦x4≦3, 1≦y4≦2, 1≦z4≦2, 1≦l1≦3, R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb, and M includes at least one of F, Cl, and Br.

[0030] Optionally, the phosphate-based sodium salt material may be specifically NaFePO4, Na3V2(PO4)3, Na2FeP2O7, Na2MnP2O7, NaCoP2O7, Na7V3(P2O7)4, Na2FePO4F, Na3V2(PO4)2F3, Na4Fe3(PO4)2(P2O7), Na4Mn3(PO4)2(P2O7), Na4Co3(PO4)2(P2O7), Na4Ni3(PO4)2(P2O7), Na7V4(PO4)(P2O7)4, etc., but not limited thereto. Preferably, the phosphate-based sodium salt material may be Na4Fe3(PO4)2(P2O7).

[0031] The shell layer material 22 used to coat the core layer material 21 contains a metal oxide, of which the metal oxide contains at least one of WO3, Al2O3, ZnO, CuO, and TiO2. Specifically, the actual oxygen atomic mass in the metal oxide is 70% to 95% of the theoretical oxygen atomic mass in the metal oxide. Optionally, the actual oxygen atomic mass in the metal oxide may be 70%, 75%, 80%, 85%, 90%, 95%, etc. of the theoretical oxygen atomic mass in the metal oxide, and is not limited thereto. The difference between the actual oxygen atomic mass in the metal oxide and the theoretical oxygen atomic mass is due to the presence of oxygen vacancy defects, that is, a part of the oxygen is lost from the original metal oxide surface to form a disordered structural layer with many oxygen vacancy defects, and a certain amount of oxygen vacancies are formed on the metal oxide surface. If there are too many oxygen vacancies, the metallicity of the material becomes too high, reducing the mechanical strength, and reducing the proportion of metal sodium salts with high ionic conductivity formed by bonding with sodium ions, thereby reducing the sodium ion conductivity. If there are too few oxygen vacancies, oxygen ions cannot move freely therein, and the electric field in the electrical resistance effect has no control over oxygen ion movement. Preferably, the actual oxygen atomic mass in the metal oxide is 85% of the theoretical oxygen atomic mass in the metal oxide.

[0032] As an option of the technical solution of the present application, the positive electrode active material with a metal oxide coating structure has better reversibility during the charge and discharge process. Metal oxide has relatively good mechanical strength and relatively high electrical conductivity, so that it can improve the electrical conductivity of the positive electrode active material, and can improve the gram capacity and dynamic properties of the positive electrode active material. Meanwhile, it can prevent the positive electrode active material from directly contacting the electrolyte, reduce the occurrence of side reactions, and improve the cycle performance of the positive electrode active material. In the positive electrode active material, the active material 2 is supported on the conductive substrate 1, and a large amount of isolated active material 2 can be connected by a one-dimensional or two-dimensional conductive network constructed outside, so that the electrical conductivity can be further improved. In addition, the oxygen-containing functional group of the conductive substrate 1 can be increased, and the oxygen-containing functional group can be used to form a stronger hydrogen bond with the shell layer material 22 on the surface of the active material 2, thereby improving the binding strength between the active material 2 and the conductive substrate 1.

[0033] In the actual application process, the mass content of the core layer material 21 in the positive electrode active material is 90% to 99%. Optionally, the mass content of the core layer material 21 in the positive electrode active material may be specifically 90%, 91%, 92%, 93%, 96%, 97%, 98%, 99%, etc., and is not limited here. If the mass content of the core layer material 21 in the positive electrode active material is too large, the proportion of metal oxide covering the core layer material is too small, the conductivity of the positive electrode active material is reduced, and the gram capacity and dynamic characteristics of the battery are affected. If the mass content of the core layer material 21 in the positive electrode active material is too small, the proportion of phosphate group sodium salt material with good cycle performance is reduced, and the cycle performance of the battery is reduced. Preferably, the mass content of the core layer material 21 in the positive electrode active material may be 95%.

[0034] The mass content of the shell layer material 22 in the positive electrode active material is 1% to 10%, and optionally the mass content of the shell layer material 22 in the positive electrode active material may be specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the thickness of the shell layer material is 50nm to 400nm, and optionally the thickness of the shell layer material may be specifically 50nm, 100nm, 150nm, 200nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc., not limited here. If the mass content and thickness of the shell layer material 22 in the positive electrode active material are too high, the shell layer will be too thick, the mass proportion of the metal oxide will be too high, and the mass proportion of the phosphate group sodium salt material with good cycle performance in the core layer will be less, which will ultimately affect the cycle performance of the battery. If the mass content and thickness of the shell layer material 22 in the positive electrode active material are too low, the metal oxide coating layer coated on the core layer material is too thin, the conductivity of the positive electrode active material is reduced, and the surface of the positive electrode active material is easily in direct contact with the electrolyte, leading to the occurrence of side reactions. Preferably, the mass content of the shell layer material 22 in the positive electrode active material is 4% to 8%, and the thickness of the shell layer material may be 100 nm to 300 nm.

[0035] As an option of the technical solution of the present application, the average particle diameter of the positive electrode active material satisfies 5 μm≦Dv50≦20 μm, and optionally, the average particle diameter Dv50 of the positive electrode active material may be specifically 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm, etc., and is not limited here. If the average particle diameter of the positive electrode active material is too small, the aggregation phenomenon of the positive electrode active material particles is likely to occur, and side reactions with the electrolyte are likely to occur. If the average particle diameter of the positive electrode active material is too large, the diffusion rate of the active ions inside the positive electrode active material is reduced, the dynamic properties are reduced, and the performance of the gram capacity of the positive electrode active material and the battery cycle performance are affected. Preferably, the particle diameter Dv50 of the positive electrode active material satisfies 8 μm≦Dv50≦15 μm.

[0036] In a second aspect, the present application provides an electrochemical device including a positive electrode sheet including the positive electrode active material described above, a negative electrode sheet, a separator, and an electrolyte.

[0037] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material of the first embodiment.

[0038] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material.

[0039] As an option of the technical solution of the present application, the negative electrode active material includes at least one of graphite, silicon material, silicon-oxygen material, tin material, tin-oxygen material, or silicon-carbon composite material.

[0040] As an option of the technical solution of the present application, the negative electrode active material layer includes an adhesive, and the adhesive includes, but is not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyfluoroethylene, ethylene oxygen-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(1,1-difluoroethylene), polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, or nylon.

[0041] As an option of the technical solution of the present application, the negative electrode active material layer further comprises a conductive material, which includes, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, metal fiber, copper, nickel, aluminum, silver, or polyphenylene derivatives, etc.

[0042] As an option of the technical solution of the present application, the negative electrode current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector.

[0043] Since sodium ions do not form an alloy with aluminum, from the viewpoint of cost reduction and weight reduction, an aluminum-based current collector including any of aluminum foil, aluminum alloy foil, and aluminum-based composite current collector is preferably used, and the aluminum-based composite current collector includes a polymer substrate and aluminum foil and / or aluminum alloy foil formed on both sides of the polymer substrate. Specifically, the aluminum-based composite current collector has a "sandwich" structure in which a polymer substrate film is located in the middle and aluminum foil is provided on both sides of the polymer substrate film, or aluminum alloy foil is provided on both sides of the polymer substrate film, or aluminum foil is provided on one side of the polymer substrate film and aluminum alloy foil is provided on the other side. The polymer substrate film may be at least one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, ethylene propylene rubber, polyformaldehyde, epoxy resin, phenol resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate. Aluminum-based composite current collectors with better ductility that helps maintain the integrity of the electrode during the sodium deposition / desorption process are preferred in this application.

[0044] As an option of the technical solution of the present application, the separator may be various materials in the art that are applied to separators in electrochemical energy storage devices, including, but not limited to, at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers.

[0045] As an option of the technical solution of the present application, the electrochemical device further comprises an electrolyte, the electrolyte comprising an organic solvent, a sodium salt and an additive.

[0046] The organic solvent of the electrolyte according to the present application may be any organic solvent known in the prior art to be used as a solvent for electrolytes. The electrolyte used in the electrolyte according to the present application is not limited and may be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art to be used as an additive for electrolytes.

[0047] In a specific embodiment, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate, fluoroethylene carbonate, propylene carbonate, propyl propionate, or ethyl propionate, but is not limited thereto.

[0048] In a specific embodiment, the sodium salt comprises at least one of an organic sodium salt or an inorganic sodium salt.

[0049] In specific examples, sodium salts include, but are not limited to, sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium difluorophosphate (NaPO2F2), sodium bis(trifluoromethanesulfonyl)imide NaN(CF3SO2)2 (NaTFSI), sodium bis(fluorosulfonyl)imide Na(N(SO2F)2) (NaFSI), sodium bisoxalatoborate NaB(C2O4)2 (NaBOB), sodium difluorooxalatoborate NaBF2(C2O4) (NaDFOB), or sodium perchlorate.

[0050] As an option of the technical solution of the present application, the electrochemical device of the present application includes, but is not limited to, all kinds of primary batteries, secondary batteries, including at least one of soft bag, rectangular aluminum case, rectangular steel case, cylindrical aluminum case, and cylindrical steel case batteries.

[0051] In a third aspect, the present application provides an electronic device comprising an electrochemical device as described above. The electrochemical device can be used to power the electronic device.

[0052] As an option of the technical solution of the present application, the electronic device includes, but is not limited to, a notebook computer, a pen-input personal computer, a mobile computer, an e-book player, a mobile phone, a mobile fax machine, a mobile copier, a mobile printer, a headphone stereo, a video recorder, an LCD television, a handy cleaner, a portable CD, a mini disc, a transceiver, an electronic organizer, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, an electric motor-assisted bicycle, a bicycle, a lighting fixture, a toy, a game machine, a clock, an electric tool, a strobe, a camera, a large-scale household storage battery, an energy storage or a sodium ion capacitor, etc.

[0053] In a fourth aspect, the present application further provides a method for producing a positive electrode active material, the method comprising the steps of:

[0054] S10: The carbon material is placed in a solution of concentrated sulfuric acid: concentrated nitric acid = 3:1 and stirred for 4 hours, washed with deionized water, filtered, and then placed in an oven and dried at 80 ° C. Among them, the pore size of the filter sieve is selected as 400 mesh.

[0055] S20: The carbon material after the above treatment is put into water and ultrasonically dispersed, then mixed and stirred with a stoichiometric ratio of iron nitrate and sodium dihydrogen phosphate solution to make it uniform, and then spray-dried to prepare precursor powder.

[0056] Among them, the carbon material after ultrasonic dispersion has an average particle size of 50 nm to 20 μm, the inlet temperature of the spray dryer is 150°C to 250°C, and the outlet temperature of the spray dryer is 80°C to 150°C.

[0057] S30: The precursor powder is roasted at a high temperature of 600°C for 6 hours, then added to a metal oxide solution and thoroughly stirred. The pH value is adjusted to coat the precursor gel on the surface of the phosphate-based sodium salt material, and the precursor is roasted at 400°C to 800°C in a hydrogen gas atmosphere. The resulting product is sieved to obtain the positive electrode active material.

[0058] Among them, the stirring time is 2 to 8 hours, the pH value after adjustment is 10 to 12, the roasting time is 4 to 10 hours, and the average particle size of the positive electrode active material after sieving satisfies 8 μm≦Dv50≦15 μm.

[0059] The positive electrode active material is finally obtained by the above-mentioned production method and by adjusting the shell layer material mass fraction, the conductive substrate mass fraction, the shell layer material type, and the positive electrode active material particle diameter.

[0060] In order for those skilled in the art to better understand the technical solution of the present invention, the present application is described in more detail below with reference to specific examples.

[0061] Example 1: (1) Manufacturing of negative electrode sheets

[0062] First, the carbon material was placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1, stirred for 4 hours, washed with deionized water, filtered, and then placed in an oven and dried at 80°C. The carbon material and polymer were added to N-methylpyrrolidone and stirred to form a uniform slurry. The slurry was applied to copper foil and dried to obtain the carbon material coating to be used. Sodium metal was placed in a stainless steel crucible in an Ar gas atmosphere and heated to 200°C to completely melt it. Then, the alloy component powder was added to the liquid sodium metal, and the mixture was thoroughly stirred for 2 hours to ensure uniform mixing of the metal powder and the sodium metal liquid, and cooled to obtain a sodium metal alloy active material. The sodium metal alloy active material was compounded on the surface of the carbon material coating by cold pressing to obtain a sodium metal negative electrode sheet.

[0063] (2) Manufacturing of positive electrode sheets 10wt% polyvinylidene fluoride adhesive was completely dissolved in N-methylpyrrolidone, and 10wt% carbon black conductive agent and 80wt% positive electrode active material were added to create a uniformly dispersed slurry. The slurry was evenly spread on the zirconium surface and transferred to a vacuum drying oven to completely dry. The resulting sheet was roll pressed and then punched out to obtain the desired wafer.

[0064] (3) Separator manufacturing A polypropylene polymer film was employed.

[0065] (4) Manufacturing of electrolyte Ethylene glycol dimethyl ether (DME) was used as the organic solvent, and thoroughly dried sodium salt NaPF6 was dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L.

[0066] (5) Manufacture of button batteries The positive electrode sheet, separator, and negative electrode sheet were stacked in order with the separator positioned between the positive electrode sheet and the negative electrode sheet to act as an insulator, and the electrolyte was added to assemble a button battery.

[0067] Specific parameters of Examples 1 to 22 and Comparative Examples 1 to 7 produced by the above-mentioned methods are shown in Table 1.

[0068] [Table 1] TIFF0007626570000002.tif220165

[0069] Performance test: (1) Resistivity of positive electrode active material: The positive electrode active material powder was measured at a pressure of 20 MPa using a powder resistance meter. (2) Gram capacity of positive electrode active material: The batteries produced in the examples and comparative examples were charged at 25° C. at a rate of 0.1 C to 4 V, and discharged at a rate of 0.1 C to 1 V, to perform a full charge / discharge test, and the discharge capacity was obtained as the gram capacity of the material. (3) Battery cycle performance: The batteries prepared in the examples and comparative examples were charged at 25°C up to 4 V at a rate of 0.1 C until the capacity of the sodium ion battery became less than 80% of the initial capacity, and then discharged at a rate of 0.1 C down to 1 V. A full charge / discharge cycle test was performed, and the number of cycles was recorded. The test results are shown in Table 2.

[0070] [Table 2]

[0071] As can be seen from Examples 1 to 4, there was a slight difference in the gram capacity and the number of battery cycles of the batteries made from the positive electrode active materials having different components. Preferably, the positive electrode active material is Na4Fe3(PO4)2(P2O7).

[0072] As can be seen from Examples 5 to 9 and Comparative Examples 1 and 2, when the mass content of the shell layer material in the positive electrode active material is within the range of 1% to 10%, the gram capacity, dynamic characteristics and cycle performance of the battery are good. When the mass content of the shell layer material in the positive electrode active material is too high, the thickness of the core layer is too high, the mass ratio of the metal oxide is too high, and the mass ratio of the phosphate group sodium salt material with good cycle performance in the core layer material becomes small, which ultimately affects the cycle performance of the battery. When the mass content of the shell layer material in the positive electrode active material is too low, the coating layer of the metal oxide coated on the core layer material is too thin, the conductivity of the positive electrode active material decreases, and the surface of the positive electrode active material is easily in direct contact with the electrolyte, which leads to the occurrence of side reactions. Preferably, the mass content of the shell layer material in the positive electrode active material is 4% to 8%.

[0073] As can be seen from Examples 10 to 14 and Comparative Examples 3 to 4, when the mass content of the conductive substrate in the positive electrode active material is within the range of 1% to 10%, the material conductivity is improved and the gram capacity of the material is improved. When the mass content of the conductive substrate in the positive electrode active material is too high, the amount of carbon material with a large specific surface area, no capacity, and low compaction density is too large, the battery capacity is small, and the energy density and cycle life of the battery are reduced. When the mass content of the conductive substrate in the positive electrode active material is too low, the conductive network between the active materials is difficult to effectively form, the conduction speed of the battery is reduced, the gram capacity of the active material is difficult to exert, and the battery life is reduced. Preferably, the mass content of the conductive substrate in the positive electrode active material is 4% to 8%.

[0074] As can be seen from Examples 15 to 17, the selection of the type of metal oxide affected the gram capacity and cycle life of the battery. Preferably, the shell layer material may be TiO2.

[0075] As can be seen from Examples 18 to 22 and Comparative Examples 5 to 6, when the average particle diameter of the positive electrode active material is within the range of 5 μm to 20 μm, the gram capacity and cycle performance of the battery are the best. When the average particle diameter of the positive electrode active material is too small, aggregation is likely to occur and side reactions with the electrolyte are likely to occur. When the average particle diameter of the positive electrode active material is too large, the diffusion rate of the active ions inside the material is reduced, the dynamic characteristics are reduced, and the gram capacity and cycle performance of the battery are affected. Preferably, the average particle diameter Dv50 of the positive electrode active material satisfies 8 μm≦Dv50≦15 μm.

[0076] As can be seen from the data of Examples 1 to 22 and Comparative Example 7, in Examples 1 to 22, the gram capacity of the positive electrode active material and the cycle life of the battery were slightly affected by changes in the conductive substrate mass fraction, the type of shell layer material, and the particle size of the positive electrode active material. However, in Comparative Example 7, which was compared, the surface of the core layer material was not coated with a shell layer material, so the conductivity of the positive electrode active material was reduced, the resistivity increased, and the gram capacity of the material was significantly reduced. In addition, the core layer material came into direct contact with the electrolyte, causing side reactions to occur, and the cycle performance of the battery was reduced.

[0077] Those skilled in the art will understand that the above embodiments are all illustrative and not restrictive. Different technical features in different embodiments can be combined to obtain beneficial effects. Those skilled in the art should understand and implement the embodiments that are modified from the disclosed embodiments after studying the drawings, the specification, and the claims. In the claims, the term "comprises" does not exclude other devices or steps, and is intended to include one / one type or multiple / multiple types of articles when the articles are not modified with numerals, and may be used interchangeably with "one / one type or multiple / multiple types of articles", and the terms "first" and "second" are not used to indicate any particular order, but are used to designate names. Any reference numerals in the claims should not be construed as limiting the scope of the claims. The functions of multiple parts described in the claims may be realized by a single hardware or software module. The presence of certain technical features in different dependent claims does not mean that these technical features cannot be combined to obtain beneficial effects. [Explanation of symbols]

[0078] 1- Conductive substrate 2-Active material 21-Core layer material 22-Shell layer material

Claims

1. A conductive substrate, and an active material having a core-shell structure composed of a core layer material and a shell layer material, the active material being distributed on the conductive substrate; wherein the conductive substrate comprises a carbon material, the core layer material comprises a phosphate-based sodium salt material, and the shell layer material comprises a metal oxide; The mass content of the shell layer material in the positive electrode active material is 1% to 10%; The mass content of the conductive substrate in the positive electrode active material is 1% to 10%; The positive electrode active material has an average particle size of 5 μm to 20 μm.

2. The metal oxide is WO 3 , Al 2 O 3 , ZnO, CuO, TiO 2 The positive electrode active material of claim 1 , comprising at least one of:

3. The positive electrode active material according to claim 1, wherein the positive electrode active material has at least one of the following characteristics (1) to (4): (1) The chemical formula of the sodium phosphate material is Na x1 R y1 (P.O. 4 ) Z1 where 1≦x 1 ≦3, 1≦y 1 ≦2, 1≦z 1 ≦3, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (2) The chemical formula of the sodium phosphate material is Na x2 R y2 (P 2 O 7 ) Z2 where 1≦x 2 ≦7, 1≦y 2 ≦3, 1≦z 2 ≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (3) The chemical formula of the sodium phosphate material is Na x3 R y3 (P.O. 4 ) Z3 (P 2 O 7 ) k3 where 1≦x 3 ≦7, 1≦y 3 ≦4, 1≦z 3 ≦2, 1≦k 3 ≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (4) The chemical formula of the sodium phosphate material is Na x4 R y4 (P.O. 4 ) Z4 M l1 where 1≦x 4 ≦3, 1≦y 4 ≦2, 1≦z 4 ≦2, 1≦l1≦3, R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb, and M includes at least one of F, Cl, and Br.

4. The sodium phosphate salt material is NaFePO 4 , Na 3 V 2 (P.O. 4 ) 3 , Na 2 FeP 2 O 7 , Na 2 MnP 2 O 7 , NaCoP 2 O 7 , Na 7 V 3 (P 2 O 7 ) 4 , Na 2 FePO 4 F, Na 3 V 2 (P.O. 4 ) 2 F 3 , Na 4 Fe 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Mn 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Co 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Ni 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 7 V 4 (P.O. 4 ) (P 2 O 7 ) 4 The positive electrode active material according to claim 1 or 2, comprising at least one of:

5. 2. The active cathode material of claim 1, wherein the mass of actual oxygen atoms in the metal oxide is 70% to 95% of the mass of theoretical oxygen atoms in the metal oxide.

6. The positive electrode active material according to claim 1 or 2, wherein the positive electrode active material has at least one of the following characteristics (5) and (7): (5) The thickness of the shell layer material is 50 nm to 400 nm. (7) The mass content of the core layer material in the positive electrode active material is 90% to 99%.

7. The positive electrode active material according to claim 1 or 2, wherein the positive electrode active material has at least one of the following characteristics (9) to (12): (9) The carbon material includes at least one of carbon nanotubes, graphene, carbon fibers, natural graphite, and artificial graphite. (10) The carbon material contains an oxygen-containing group, and the oxygen-containing group is at least one type selected from a carboxyl group, a hydroxyl group, and an ether group. (11) The carbon material contains an oxygen-containing group, and the mass content of oxygen atoms in the carbon material is ≧0.1%. (12) The conductive substrate is a carbon material.

8. The positive electrode active material according to claim 1, wherein the positive electrode active material has at least one of the following characteristics (13) and (15): (13) The positive electrode active material has a resistivity of 0.005 Ω·cm to 100 Ω·cm at a pressure of 20 MPa. (15) The gram capacity of the positive electrode active material is 100 mAh / g to 180 mAh / g.

9. An electrochemical device comprising a positive electrode sheet containing the positive electrode active material according to any one of claims 1 to 8, a negative electrode sheet, a separator, and an electrolyte.

10. An electronic device comprising the electrochemical device of claim 9.

Citation Information

Patent Citations

  • Polyanion-based positive electrode active material and method of manufacturing the same

    JP2018006156A

  • Olivine sodium iron phosphate with polymer coating, sodium iron battery comprising the same as cathode material, and process thereof

    KR1020160136809A

  • Electrode Active Material and Method for Preparing the Same

    KR1020200109991A

  • Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    WO2017195332A1